Peningkatan kualitas sumber daya manusia aparatur kelurahan pelabuhan dagang Kecamatan Tungkal Ulu Kabupaten Tanjung Jabung Barat - Rahmadi, Selamet; Parmadi, Parmadi; Hastuti, Dwi (Studium: Jurnal Pengabdian Kepada Masyarakat, 2025)
The service activities aim to improve the quality of understanding and capability of human resources in Port Dagang Subdistrict, Tungkal Ulu Subdistrict, West Tanjung Jabung Regency related to basic government knowledge, management skills and technical capabilities in carrying out government duties and responsibilities in development in order to provide the best public services for the community. The service method uses community-based, persuasive, educative, participatory and normative development methods. This method is carried out to create quality human resources in the sub-district in administering government, both in the fields of law enforcement, openness, justice, efficiency and effectiveness as well as being sensitive to problems that arise. The results of this community service indicate an improvement in the understanding and knowledge of sub-district officials, as well as a strengthening their capacity to handle various community issues and carry out tasks in order to enhance the quality of public services optimally.